Communication Technology Planning for Power Terminal Communication Access Networks in the “14th Five-Year Plan” Based on Analytic Hierarchy Process - Qing WU; Yundi WANG; Lingkang ZENG; Yunxiao SUN; Minlin CHEN (Zhongguo dianli)
In the “13rd Five-Year Plan”, the construction, operation and management of power terminal communication access networks were mainly led by each business department, which resulted in some problems such as lacking of overall planning and scientific guidance for the selection of communication technologies, as well as repeat construction of communication networks. The energy internet in the “14th Five-Year Plan” will have the characteristics of terminal integration, business integration and network integration. A communication technology planning model for access networks is established based on analytic hierarchy process for the typical scenarios of multi-business integration. The principles for selecting telecommunication technology are proposed for power terminal communication access networks for different power supply areas, which can provide a reference for the planning and construction of power terminal communication access networks in the “14th Five-Year Plan”.